2020
DOI: 10.1007/s12011-020-02215-7
|View full text |Cite
|
Sign up to set email alerts
|

Lead (Pb) Accumulation in Human THP-1 Monocytes/Macrophages In Vitro and the Influence on Cell Apoptosis

Abstract: In this study, we investigated the ability of THP-1 monocytes and macrophages to accumulate lead (Pb) in vitro, relative to Pb concentration and length of exposure. Moreover, we also evaluated the effect of Pb accumulation on cell viability and apoptosis. THP-1 monocytes and macrophages were cultured in the presence of Pb at 1.25 μg/dL, 2.5 μg/dL, 5 μg/dL, and 10 μg/dL. Pb accumulation was examined by inductively coupled plasma and confocal microscopy. The influence of Pb on cell viability, apoptosis, and necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 96 publications
1
8
0
Order By: Relevance
“…Our study revealed that Pb exposure greatly inhibited cell viability in PC12, while black soybean peptides can reduce the damage of lead exposure to cell viability. In the latest research on the effects of Pb accumulation on cell viability and apoptosis, it was shown that environmental exposure to low concentrations of Pb might greatly impair the function of macrophages, and an increase in the number of apoptotic cells may cause the occurrence of many diseases in the organism [ 28 ]. It has been found that when intracellular ROS increases, cell viability decreases, especially when the metal mixture is used as a promoter stimulus [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study revealed that Pb exposure greatly inhibited cell viability in PC12, while black soybean peptides can reduce the damage of lead exposure to cell viability. In the latest research on the effects of Pb accumulation on cell viability and apoptosis, it was shown that environmental exposure to low concentrations of Pb might greatly impair the function of macrophages, and an increase in the number of apoptotic cells may cause the occurrence of many diseases in the organism [ 28 ]. It has been found that when intracellular ROS increases, cell viability decreases, especially when the metal mixture is used as a promoter stimulus [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yuan et al said SOD and GSH/GSSG quickly cleared the ROS within cells to keep the stability of the internal structures of the cells and tissue. Otherwise, high ROS levels will disrupt the cell balance [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, cadmium could also induce hepatocyte apoptosis and tissue damage through inflammatory reaction [ 89 ]. Even at very low lead concentrations, Pb was equally toxic to monocytes and macrophages, which shows a decline in cell viability and an increase in the number of apoptotic cells [ 90 ]. Zhou also found that lead could increase the expression of PPARγ and stimulate the cleavage of caspase-3 and PARP to induce cytotoxicity [ 91 ].…”
Section: Major Toxicity Mechanisms Induced By Mycotoxins and Heavy Me...mentioning
confidence: 99%
“…These far exceeded the maximum permissible limit of 0.01 ppm (WHO) and 0.05 ppm (USEPA) for drinking water. The maximum permissible limit is of concern as Pb is a toxic metal that can cause impairment to nervous systems (particularly in children) which can result in brain and blood disorders (Metryka et al, 2021). Hematological damage is well noted with high Pb absorption, which is one of the most serious and important biochemical effects of Pb in drinking water (Ehi-Eromosele and Okiei, 2012).…”
Section: Heavy Metals Status In the Water And The Allowable Concentra...mentioning
confidence: 99%